Digital sustainability: Dimension exploration and scale development - Yixuan Wang; Ying Yu; Asif Khan (Acta Psychologica)
Digital sustainability is crucial in helping businesses achieve Sustainable Development Goals by integrating digitalization with sustainability to promote green growth. Despite its growing importance, significant gaps exist in its conceptual structure and measurement. This study identifies key dimensions of digital sustainability—empowerment, leadership, and integration—through a comprehensive literature review, grounded theory, and synergy effects theory. This study developed measurement scales for each dimension and empirically validated them using data from 240 valid questionnaires analyzed with SPSS and AMOS software. The findings clarify the conceptual makeup of digital sustainability and confirm the reliability and validity of the developed scales. This provides a useful quantitative tool for assessing digital sustainability and enhances our understanding of its conceptual framework.